(untitled) (Sains Humanika, 2009)
Mukim Kuala Besut is one of the main fishing areas in Terengganu. Numerous fishing facilities and development programs have been implemented by the Government to support the families of fishermen. However, most of the young generation in Mukim Kuala Besut were not interested in fishing industry. The objective of the study is to explore the interest of youth in a fishing career in Mukim Kuala Besut. A sampel of 365 young males, aged between 18 to 40 years old, children of Malay fishermen were chosen for this study. The results of the study showed that the level of youths’ interest in fishing career was moderate. Three main factors influencing their interest were training programs, benefits and marketing.